2015
DOI: 10.1007/s10495-015-1175-4
|View full text |Cite
|
Sign up to set email alerts
|

Phosphocreatine protects endothelial cells from oxidized low-density lipoprotein-induced apoptosis by modulating the PI3K/Akt/eNOS pathway

Abstract: Endothelial apoptosis triggered by oxidized low-density lipoprotein (oxLDL) can accelerate the progression of endothelial dysfunction atherosclerosis. Phosphocreatine (PCr) is a natural compound, which has been used in cardiac disease and cardiopulmonary resuscitation. However, its protective effects on atherosclerosis and its mechanism have not been clarified. In the present study, we investigated the anti-apoptotic effect of phosphocreatine in human umbilical vein endothelial cells (HUVECs) exposed to oxLDL … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
33
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(40 citation statements)
references
References 45 publications
7
33
0
Order By: Relevance
“…The activation of arginase II by oxLDL was through a LOX-1 dependent RhoA/ROCK pathway [29], which was consistent with the observation that arginase II was dissociated from microtubules by oxLDL [28]. Phosphocreatine antagonized the apoptotic effect of oxLDL by activating PI3K/Akt/eNOS pathway and NO production in HUVECs [30]. Meanwhile, p38MAPK/NF- κ B pathway has been shown to be strongly activated by oxLDL and served as an effective target for intervention [31, 32].…”
Section: Discussionsupporting
confidence: 63%
“…The activation of arginase II by oxLDL was through a LOX-1 dependent RhoA/ROCK pathway [29], which was consistent with the observation that arginase II was dissociated from microtubules by oxLDL [28]. Phosphocreatine antagonized the apoptotic effect of oxLDL by activating PI3K/Akt/eNOS pathway and NO production in HUVECs [30]. Meanwhile, p38MAPK/NF- κ B pathway has been shown to be strongly activated by oxLDL and served as an effective target for intervention [31, 32].…”
Section: Discussionsupporting
confidence: 63%
“…Activated Akt could inhibit the expression of pro‐apoptotic proteins, such as bax, caspase‐9, and caspase‐3 (Hwang et al, ). Moreover, Akt is an important regulator of eNOS activity in vessels (Ahsan et al, ). eNOS regulates the release of NO to promote endothelial cell migration and neovascularization (Fu, Wang, Guo, Xu, & Wu, ).…”
Section: Discussionmentioning
confidence: 99%
“…The current study suggests that Klotho may rescue ox-LDL-induced inhibition of NO production through the activation of Akt/eNOS pathway in HUVECs. Similarly, some natural compounds also protect endothelial cells from ox-LDL-induced apoptosis by modulating the PI3K/Akt/eNOS pathway [44]. In contrast, many studies indicated that decreased NO is another key mechanism underlying endothelial dysfunction, which is interrelated with decreased expression of the Klotho gene [33, 4547].…”
Section: Discussionmentioning
confidence: 99%